The epigastric heteropagus conjoined twins - Abubakar, Auwal Mohammed; Ahidjo, Ahmed; Chinda, John Y.; Tahir, Chubado; Abubakar, Sadiq; Adamu, Sani A.; Pindiga, Umaru H. (Elsevier, 2011)
Conjoined twins are rare and are classified as symmetrical or asymmetrical, in which a member, the host (autosite), is near normal and bears the parasite, which is incomplete, smaller, and fully dependent for growth on it. This form of conjoined twins is referred to as heteropagus and when attached to the epigastrium of the autosite is called epigastric heteropagus. Only 44 cases of epigastric heteropagus twins have been previously reported in the world literature. We hereby report the successful separation of a pair of heteropagus twins. (C) 2011 Elsevier Inc. All rights reserved.